2010
DOI: 10.1080/17441690903334943
|View full text |Cite
|
Sign up to set email alerts
|

Implementing integrated disease surveillance and response: Four African countries' experience, 1998–2005

Abstract: The Integrated Disease Surveillance and Response (IDSR) strategy was developed by the Africa Regional Office (AFRO) of the World Health Organisation (WHO) and proposed for adoption by member states in 1998. The goal was to build WHO/AFRO countries' capacity to detect, report and effectively respond to priority infectious diseases. This evaluation focuses on the outcomes in four countries that implemented this strategy. Major successes included: integration of the surveillance function of most of the categorica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 8 publications
16
61
0
Order By: Relevance
“…EVD surveillance support functions and response preparedness The findings from this study demonstrate that supervision for surveillance at the district or hospital is rather irregular and also not for Ebola, which supports previous findings (13,14). Although there is some improvement in the training and employment of disease control officers, they remain inefficient and ineffective.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…EVD surveillance support functions and response preparedness The findings from this study demonstrate that supervision for surveillance at the district or hospital is rather irregular and also not for Ebola, which supports previous findings (13,14). Although there is some improvement in the training and employment of disease control officers, they remain inefficient and ineffective.…”
Section: Discussionsupporting
confidence: 76%
“…These problems range from validity and quality of suspected EVD data; to problems regarding specimen taking, analysis, and confirmation and feedback; to problems of inadequate resources. Though some countries in SSA have shown some improvements in disease surveillance activities with increased potential for rapid dissemination of information (11,14,16,31), findings from the current study in northern Ghana rather revealed that late case detection and delays to provide health care services to suspected Ebola patients at health facilities are common practices leading to preventable deaths. There have been reported cases of clinically diagnosed EVD in northern Ghana.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Lack of on-the-job training for staff who did not attend the training and lack of support through posttraining follow-up and supportive supervision were weaknesses in the intervention. These systemic challenges, reported in other IDSR ( 13 ) and mHealth surveillance ( 14 ) projects, must be addressed to avoid compromising the sustainability of such interventions. Finally, attrition of health workers exposed to the intervention and lack of paper-based tools explain only part of our results.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 Because of the importance of linking surveillance to public health action, the strategy was later renamed as integrated disease surveillance and response. Action thresholds were then defined for the common epidemic-prone infectious diseases, so Europe PMC Funders Author Manuscripts that epidemic investigation and response could be triggered in settings where the thresholds were exceeded.…”
Section: Components Of Surveillance and Responsementioning
confidence: 99%